Peran Guru Berkompetensi Sosial Emosional dalam Pembelajaran Pendidikan Pancasila untuk Membangun School Well-Being di SMA Negeri 5 Semarang - Susilowati, Indah; Haryati, Titik (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to analyze the role of socially emotionally competent teachers in Pancasila Education learning to build school well-being at SMA Negeri 5 Semarang. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results showed that teachers with social emotional competence play an important role in implementing Pancasila Education learning to build school well-being at SMA Negeri 5 Semarang. Teachers with social emotional competence are able to create a safe and comfortable learning environment, build positive relationships with students, and encourage students to develop character and national insight. Social emotional competencies that are important for teachers in implementing Pancasila Education learning include self-awareness, social awareness, self-regulation, relationship skills, and responsible decision-making. Teachers with high social emotional competence are able to manage their own emotions, build positive relationships with students, and create a conducive learning environment. This study recommends that teachers at SMA Negeri 5 Semarang continue to improve their social emotional competence in order to effectively implement Pancasila Education learning and build school well-being.